WORKSHOP-INTENSIVE HOUSING AS A STRATEGY FOR URBAN COMMUNITY EMPOWERMENT: A CASE STUDY OF THE PISTOP PROGRAM IN LIDAH KULON SURABAYA - Nauval Shafy i Putra Marsud; Eny Haryanti; Ika Devy Pramudiana; Amirul Mustofa (Journal Publicuho, 2025)
This study aims to describe the form of community empowerment through the Workshop Intensive House Program (WIHP) in the Pistop area, Lidah Kulon, Surabaya. This program is an initiative of the Surabaya City Government to overcome the problem of unemployment and improve the work skills of residents through automotive technical training. This research results in a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study show that the WIHP Bengkel program has had a positive impact on improving individual technical skills, forming community working groups, and increasing residents' income independently. However, the implementation of the program still faces various challenges, such as limited tools, the absence of institutional legality, and suboptimal coordination between stakeholders. These findings are reinforced by research (Hairunisya et al., 2023), which shows that integrated technical training is able to increase the economic capacity of communities if supported by strong institutions and collaborative strategies across sectors. Therefore, a more inclusive participatory approach, as well as sustained institutional support, is needed to ensure the effectiveness of community-based empowerment programs.